The other side of prospect : a story of violence, injustice, and the American city - Dawidoff, Nicholas (W.W. Norton & Company, 2022)
"A landmark work of intimate reporting on inequality, race, class, and violence, told through a murder and intersecting lives in an iconic American neighborhood. One New Haven summer evening in 2006, a retired grandfather was shot point-blank by a young stranger. A hasty police investigation culminated in innocent sixteen-year-old Bobby being sentenced to prison for thirty-eight years. New Haven native and acclaimed author Nicholas Dawidoff returned home and spent eight years reporting the deeper story of this injustice, and what it reveals about the enduring legacies of social and economic disparity. In The Other Side of Prospect, he has produced an immersive portrait of a seminal community in an old American city now beset by division and gun violence. Tracing the histories of three people whose lives meet in tragedy--victim Pete Fields, likely murderer Major, and Bobby--Dawidoff indelibly describes optimistic families coming north from South Carolina as part of the Great Migration, for the promise of opportunity and upward mobility, and the harrowing costs of deindustrialization and neglect. Foremost are the unique challenges confronted by children like Major and Bobby coming of age in their "forgotten" neighborhood, steps from Yale University. After years in prison, with the help of a true-believing lawyer, Bobby is finally set free. His subsequent struggles with the memories of prison, and his heartbreaking efforts to reconnect with family and community, exemplify the challenges the formerly incarcerated face upon reentry into society and, writes Reginald Dwayne Betts, make this "the best book about the crisis of incarceration in America." The Other Side of Prospect is a reportorial tour de force, at once a sweeping account of how the injustices of racism and inequality reverberate through the generations, and a beautifully written portrait of American city life, told through a group of unforgettable people and their intertwined experiences"--